PENETAPAN KADAR CAPSAICIN BEBERAPA JENIS CABE (Capsicum sp) DI INDONESIA - U. Sumpena (Universitas Wahid Hasyim, 2013)
Capsaicin – the major active principle in chillies is an alkaloid, which cause the ‘hot’ sensation when contact with the skin and muscous membrane. At least twenty varieties of consumable chillies known in Indonesia, and each of them has different degree of ‘hotness’. This degree of ‘hotness’ was though due to capsaicin content in chillies. The study was carried out to chemically quantitate the capsaicin content of sixteen varieties of Indonesian chillies. Capsaicin was extracted from the dried chillies powder. The organic extract was analyzed by Thin layer Chromatography with silica gel F 254 as supportive medium and diethyl either as mobile phase. The determination of capsaicin was conducted spectrophotometrically with Gibb’s reagent as color developer. The capsaicin content of the examined chillies varieties ranged from 0,07 – 1,60 %, with the highest content was found in Rawit Kalimantan. The organoleptic between the capsaicin content of chillies send the Scoville Heat Units. Key words : capsaicin, capsicum, organoleptic